2010
DOI: 10.1227/01.neu.0000362033.38035.25
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Tumors of the Anterolateral Skull Base

Abstract: It is our belief that anterolateral skull base malignancies comprise a distinct group of tumors. These lesions should be analyzed separately from central anterior skull base lesions and temporal bone malignancies. With a multimodality treatment protocol, acceptable survivals may be obtained that are comparable to results that have been reported for tumors involving less difficult areas of the skull base.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
24
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 22 publications
4
24
2
Order By: Relevance
“…This aspect was shown to be a significant negative prognostic factor of overall survival, and it may be explained by the presence of a more aggressive disease. Our 68% rate of negative resection margins is in accordance with previous reported series . However, it was not found to be a significant prognostic factor in the 32% of patients with positive margins.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This aspect was shown to be a significant negative prognostic factor of overall survival, and it may be explained by the presence of a more aggressive disease. Our 68% rate of negative resection margins is in accordance with previous reported series . However, it was not found to be a significant prognostic factor in the 32% of patients with positive margins.…”
Section: Discussionsupporting
confidence: 92%
“…The pathologic processes and lesions that may involve the ITF are variable, thus the outcome of treatment varies accordingly. There are only few published studies that selectively investigated tumors involving the ITF . Givi et al reported 43 patients who underwent tumor resection from the ITF using a combination of a pterional craniotomy with craniofacial resection or a bifrontal craniotomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A tendency of spread through perineural spaces is a common characteristic of some malignant tumors of the head and neck origin, including but not limited to, sarcomas, squamous cell carcinomas, and adenoid cystic carcinomas . The trigeminal nerve involvement at the floor of the middle cranial fossa is not uncommon.…”
Section: Discussionmentioning
confidence: 99%
“…3,4,27,43,45 Standard therapy for this malignancy has most commonly included a strategy of local resection followed by adjuvant radiation therapy. 6,13,16,17,23,24,28,30,35,38,39,43,46,47,52 Chemotherapy using agents such as carboplatinum and paclitaxel has been used, but with limited results. 2,11,12,15,26,27,36,41,44,[48][49][50] ACC can arise in any salivary gland, both major and minor.…”
mentioning
confidence: 99%